Growth processes of Italian manufacturing firms - Alex Coad; Rekha Rao; Federico Tamagni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2010)
This paper presents a multidimensional empirical analysis of firm growth. Exploiting census data on Italian manufacturing firms, 1989-1997, we estimate a reduced-form VAR to analyze the co-evolution of employment growth, sales growth, growth of profits and labour productivity growth. Our main findings suggest that (i) employment growth precedes sales growth; (ii) productivity growth lacks any strong association with subsequent growth of the other indicators; (iii) profits growth represents the 'absorbing dimension' of the growth processes. This picture contrasts with 'accelerator models', predicting sales are the driver of the growth process, and is also at odds with theories of firm-industry evolution assuming productivity or profits advantages to be the driver of strong market selection/reallocation mechanisms. Instead, the findings reveal the existence of (weak) Penrose and (strong) Kaldor-Verdoorn effects, and more generally convey the view that employment growth is the key driver of firm expansion, while profits, once made, are not reinvested.
Keywords: C30; D20; L20; L25; 330; Firm Growth; Panel VAR; Employment Growth; Industrial Dynamics; Productivity Growth; Industrie; Unternehmenswachstum; Beschäftigungseffekt; Arbeitsproduktivität; VAR-Modell; Panelforschung; Italien